Problems In The Application Of Tajweed In Reading The Qur'an At Senior High School (SMA) Alwashliyah 1 Medan - Muhajirin Ansori Situmorang (Albayan Journal of Islam and Muslim Societies, 2024)
Abstract: Learning the Qur'an is an obligation for every Muslim because its laws are laid down by scholars derived from the Qur'an and hadith. Studying it in theory is the law of fardhu kifayah, while reading the Qur'an according to the rules of tajweed, the law is fardhu 'ain. Reading the Quran certainly should not be careless without paying attention to the rule of law. Reading it incorrectly can result in a change in the meaning of the Qur'an. Although there are also mistakes that do not change the meaning, both of them are still punished haram by the scholars. At SMA Alwashliyah 1 Medan, there are still many problems in the application of tajweed in reading the Quran. Starting from internal factors to external factors. This obstacle is certainly an obstacle that must be faced by finding solutions so that Qur'an learning can run well. This study used qualitative research. Field data acquisition using conservation techniques, interviews and documentation. The result of this study is that there are still many problems of students who are not able to read the Quran correctly. In overcoming this problem, Qur'an teachers make various efforts, both in methods, strategies, and other efforts to achieve effective and efficient Qur'an learning.    Abstrak: Belajar Al-Qur'an adalah kewajiban bagi setiap Muslim karena hukumnya ditetapkan oleh para ulama yang berasal dari Al-Qur'an dan hadis. Mempelajarinya secara teori adalah hukum fardhu kifayah, saat membaca Al-Qur'an sesuai dengan aturan tajwid, hukumnya adalah fardhu 'ain. Membaca Al-Qur'an tentu tidak boleh sembarangan tanpa memperhatikan supremasi hukum. Membacanya secara tidak benar dapat mengakibatkan perubahan makna Al-Qur'an. Meski ada juga kesalahan yang tidak mengubah makna, keduanya tetap dihukum haram oleh para ulama. Di SMA Alwashliyah 1 Medan, masih banyak permasalahan dalam penerapan tajwid dalam membaca Al-Quran. Mulai dari faktor internal hingga faktor eksternal. Kendala ini tentunya menjadi kendala yang harus dihadapi dengan mencari solusi agar pembelajaran Al-Qur'an dapat berjalan dengan baik. Penelitian ini menggunakan penelitian kualitatif. Akuisisi data lapangan menggunakan teknik konservasi, wawancara dan dokumentasi. Hasil dari penelitian ini adalah masih banyak permasalahan siswa yang tidak dapat membaca Al-Qur'an dengan benar. Dalam mengatasi permasalahan tersebut, guru Al-Qur'an melakukan berbagai upaya, baik dalam metode, strategi, maupun upaya lainnya untuk mencapai pembelajaran Al-Qur'an yang efektif dan efisien.